Peran Kepala Sekolah Dalam Manajemen Berbasis Sekolah (MBS) Untuk Meningkatkan Profesionalisme Guru Di SD Negeri 1 Mata Ie Aceh Besar - Sardina Waty; sulaiman Sulaiman; Nurmasyitah Nurmasyitah (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study aims to determine the professionalism of teachers through the Principal's Role in School-Based Management (SBM) at SD Negeri 1 Mata Ie Aceh Besar. The approach used in this research is qualitative with descriptive type. This research was conducted at the 1 Mata Ie Aceh Besar State Elementary School located in Aceh Besar, Darul Imarah sub-district, Aceh Besar district. The subjects of this study consisted of the principal and three classroom teachers. Data collection techniques were carried out by observation and interviews. Data processing uses data reduction, data presentation, and drawing conclusions. SBM school-based management is management that provides autonomy to improve teacher professionalism and improve the quality of education. The principal's role in improving teacher professionalism includes being a leader such as encouraging a teacher to teach voluntarily, providing guidance to teachers, motivators providing exemplary attitudes to teachers and students, being managerial in planning and implementation in decision making, and administrators have carried out proper planning. designed at the time of decision making. Researchers through observations and interviews with teachers, in implementing it has been going well. the principal is ready to check properly such as directing teachers in teaching, teacher lesson plans before carrying out learning, and directing teachers to use strategies, learning models, and learning media. From the results of the study, it can be said that with the SBM program the professionalism of teachers has increased through the role of the principal well.